2015
DOI: 10.1016/j.bjorl.2015.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of neutrophil-to-lymphocyte ratio and mean platelet volume in sudden hearing loss

Abstract: Neutrophil-to-lymphocyte ratio is a quick and reliable indicator regarding diagnosis and prognosis of sudden hearing loss; on the other hand, mean platelet volume may be considered a less important indicator in this aspect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 43 publications
0
45
2
1
Order By: Relevance
“…In particular, Seo et al (2014) and Kum et al (2015) showed lower values of lymphocyte count in patients with less than 15 dB HL of hearing gain with respect to the initial hearing loss. Masuda et al (2012), _ Ikinciogullar{ et al (2014) and Quaranta et al (2015) instead did not observe any correlation between lymphocyte count and recovery rate.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In particular, Seo et al (2014) and Kum et al (2015) showed lower values of lymphocyte count in patients with less than 15 dB HL of hearing gain with respect to the initial hearing loss. Masuda et al (2012), _ Ikinciogullar{ et al (2014) and Quaranta et al (2015) instead did not observe any correlation between lymphocyte count and recovery rate.…”
Section: Discussionmentioning
confidence: 82%
“…On the contrary, Sagit et al (2013) and Seo et al (2014) analysing, respectively, haematological data of 31 and 348 SSNHL patients evidenced a significant difference in PC values between subjects with and without SSNHL. Furthermore, Yasan et al (2013), Wittig et al (2014), Quaranta et al (2015), Kum et al (2015) did not recognise PC as prognostic factor for hearing recovery (p40.05).…”
Section: Discussionmentioning
confidence: 95%
“…6, 21 On the other hand, given that according to previous studies, cardiac ischemic events are associated with some platelet parameters such as mean platelet volume.…”
Section: Discussionmentioning
confidence: 98%
“…It is valuable as expensive inflammatory markers, such as IL-6, IL-1β, IL-8, and TNF-α 18 . In recent studies, the value of NLR has been also studied in the diagnosis and the prognosis of ISSHL [19][20][21][22][23][24] . The higher levels of NLR in unrecovered patients of ISSHL was explained with the higher inflammation situation of these patients 19,23 .…”
Section: Biochemical and Hematological Analysesmentioning
confidence: 99%
“…In recent studies, the value of NLR has been also studied in the diagnosis and the prognosis of ISSHL [19][20][21][22][23][24] . The higher levels of NLR in unrecovered patients of ISSHL was explained with the higher inflammation situation of these patients 19,23 . Therefore, in these studies, NLR was suggested as a quick and reliable indicator for diagnosis and prognosis of ISSHL [19][20][21]23 .…”
Section: Biochemical and Hematological Analysesmentioning
confidence: 99%